Sindroma Bangkok : Kompas, Jakarta post, Bisnis Indonesia & Majalah ayam & telur - Nasoetion, Andi Hakim (Pusat Studi Pembangunan, Institut Pertanian Bogor, 1995)
Improvement of quality and marketing of Indonesian agricultural products; collection of articles.